ANALISA KECEPATAN SISA PROYEKTIL BERHIDUNG LANCIP DENGAN METODE ELEMEN HINGGA - Pujo Wahyu Utomo; Ismoyo Haryanto; Rusnaldy Rusnaldy (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Ballistic tests are needed to determine the phenomenon that occurs due to the penetration of bullets on the target material. Nowadays the development of ballistic tests aimed to design a bullet-proof material to be able to reduce as much as possible bullets energy which generated by the firing process. 3D simulation has been performed to study the ballistic resistance of ductile target collides with projectile with conical nose at normal collision. The angle formed between the target sheet and the projectile is 90o.The first simulation used 81,06 grams 4340 aluminum steel projectile which has Caliber-Radius-Head (CRH) 3,0, with 88.9 mm long and 12.9 mm in diameter. This projectile collides with the target plate which has a 6061-T6 aluminum material with a thickness of 26.3 mm. The second simulation used Weldok 460 E steel plate as a target with a thickness of 12 mm and a diameter of 500 mm, collides with hardened Arne projectile with 20 mm in diameter and 98 mm in length. The third simulation used 608 mm aluminum plate with 608 mm length of the plate.The results of this simulation are the ballistic limit velocities, and the results are later compared with the reference journal. The simulation of aluminum plate had 233 m/s ballistic limit velocity, the simulation of Weldox 460 E plate had 227 m/s ballistic limit velocity, and the simulation of 608 mm aluminum plate had 230 m/s ballistic limit velocity. Failures that occur on the aluminum plate 608 mm is because the rear surface of the plate occurs wave reflection. For further research is expected to examine ballistic limit velocity with other firing angle